2014
DOI: 10.1080/10410236.2014.923086
|View full text |Cite
|
Sign up to set email alerts
|

Communication Theory and Health Communication Practice: The More Things Change, the More They Stay the Same1

Abstract: This article considers one of the most fundamental concerns of health communication scholars, educators, and professionals--the relationship between communication theory and health communication practice. Assertions about the important role of communication in health care--as both problem and potential solution--have become increasingly common, as have discussions of theoretical advances in communication and health communication. That said, the fundamental challenge of improving provider-patient communication,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 33 publications
2
62
0
4
Order By: Relevance
“…Communication is an important topic, perceived as inevitable for providing effective and high quality health care among both patients and health care professionals. Research evidence has shown the import role of communication in a number of health care related outcomes, such as better utilization of health care, better patient compliance, higher social support, or improved clinical outcomes and prevention [1][2][3]. Research findings also showed that contrary to expectations, most patients did not report that their most memorable experiences were related to the clinical or technical quality of the care they received, but rather they were associated with the personal attitude or interpersonal communication by health care professionals [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication is an important topic, perceived as inevitable for providing effective and high quality health care among both patients and health care professionals. Research evidence has shown the import role of communication in a number of health care related outcomes, such as better utilization of health care, better patient compliance, higher social support, or improved clinical outcomes and prevention [1][2][3]. Research findings also showed that contrary to expectations, most patients did not report that their most memorable experiences were related to the clinical or technical quality of the care they received, but rather they were associated with the personal attitude or interpersonal communication by health care professionals [1].…”
Section: Introductionmentioning
confidence: 99%
“…Research evidence has shown the import role of communication in a number of health care related outcomes, such as better utilization of health care, better patient compliance, higher social support, or improved clinical outcomes and prevention [1][2][3]. Research findings also showed that contrary to expectations, most patients did not report that their most memorable experiences were related to the clinical or technical quality of the care they received, but rather they were associated with the personal attitude or interpersonal communication by health care professionals [1]. Street et al [2] conclude that the pathways through which the quality of clinicians/ patient communication can influence the health outcomes may be both direct and indirect.…”
Section: Introductionmentioning
confidence: 99%
“…A key point in using healthy behavior promotion channels is that the communication should create appropriate cognitive responses in clients. For instance, if the communication arouses negative thoughts or imaginations about the message sender, clients will not be persuaded to engage in the intended behavior [41]. One of the aims of SM-based interventions is to use user-preferred channels to make a given product, its price, and its place pleasurable to its clients [42].…”
Section: Discussionmentioning
confidence: 99%
“…For this qualitative study, the interventions were not placed within a theoretical framework. Any future research, however, would benefit from the explicit incorporation of a theoretical framework to measure and describe mechanisms of change: patient–clinician communication theory [ 57 , 58 ] or communication constructs integrated with theories of self-efficacy [ 59 ] and enablement [ 60 ] appear relevant.…”
Section: Discussionmentioning
confidence: 99%